Homossexualismo: Uma abordagem bíblico-teológica - Wiese, Werner (Vox Scripturae - Revista Teológica Internacional, 2010)
Homosexualism is an extremely polemic topic. During centuries and even millenniums it was kept clandestinely. But, starting some decades ago it came out public and over time it occupies, more and more space on media and on society in general, including the religious society, specifically the Christian one. On the present article, first there is an exposition of biblical texts from the Old and the New Testament on which the topic of the matter is in perspective. Next, there is a linguistic and theological analysis of the data on the text, listening the arguments and counter arguments. It´s seen that both the texts of the Old and the New Testament point to the same direction, which is: the practice of homosexuality can´t be biblically legitimated, but on the contrary. The difference between the Old and the New Testament is that the first limits itself to ban the homosexual practice and punish it severely in the interior of God´s people, and the New Testament points to the gospel that not only forgives sin, but wants to restore the person. With these findings, the problems that homosexualism can bring aren´t solved, but starting at the gospel there is the poimen work – the pastoral care that opens perspectives to meaningful changes for persevering volunteers.
Keywords: Homosexualism; Homosexualism under the optic of the OT and the NT; Homosexualism and pastoral care